Plant Protection Services in Nepal: A Discourse and Assessment - Pokharel, Surendra P.; Adhikari, Debraj; G.C., Yubak Dhoj (Journal of the Plant Protection Society, 2018)
Agricultural production has been challenged by various biotic and abiotic factors in Nepal. Losses incurred by different insect pests and diseases are remarkable. As a counter measure, Government of Nepal has implemented various activities through extension, research and academic institutions. Integrated Pest Management (IPM) has been the central approach of plant protection in Nepal. It was initiated in 1997 with an aim to reduce the excessive and injudicious use of chemical pesticides to enhance the crop production, paying due attention on gender mainstreaming, and social inclusion. Besides, plant clinic program is gaining popularity in Nepal to provide plant health extension advisory services. Being a signatory country of Rotterdam Convention and Stockholm Convention, Nepal has imposed ban on sixteen different types of chemical pesticides including persistent organic pollutants (POPs). Botanicals and bio-pesticides are also used in agriculture to manage pests and diseases of crops in Nepal. So far, different 2275 pesticides have been registered by Pesticide Management and Registration Division (PMRD). National Plant Quarantine Program has been regulating the risks of entry, establishment and spread of harmful pest and plant diseases. Until now, quarantine pest of 18 commodities are identified. Strong research back up and coordination among the working partners are realized at wider level. This article assesses the status of the plant protection services and find way forward for strategic implementation of the plant protection services in Nepal.